2015
DOI: 10.17584/rcch.2015v9i1.3753
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescencia como indicador de estrés en <i>Helianthus annuus</i> L. Una revisión

Abstract: Plantulas de tomate.Foto: Álvarez-Herrera. RESUMENEl girasol es una Asteraceae con alto potencial como planta de corte. Esta planta está expuesta a una amplia fluctuación de condiciones ambientales como luz, temperatura, suministro de agua y nutrientes. Estas condiciones pueden generar estrés sobre las plantas. El girasol presenta resistencia a la sequía, bajas y altas temperaturas. Los efectos del estrés dependen de la intensidad y de la etapa fenológica en que se presente. La fluorescencia puede ser emplead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 49 publications
(72 reference statements)
3
7
0
6
Order By: Relevance
“…The effective photochemical quantum yield of PSII (Y II ) indicates the part of the energy absorbed by chlorophyll, which is associated with PSII and is used in the photochemical activity, evidencing the sum of transported electrons and, thus, becomes an indicator for photosynthesis (Lichtenthaler et al, 2005;Jiménez-Suancha et al, 2015). Overall, the Y II of the waterlogged lulo plants decreased with the increased stress, as Else et al (2009) observed in tomatoes.…”
Section: Chlorophyll Fluorescence Parametersmentioning
confidence: 96%
See 1 more Smart Citation
“…The effective photochemical quantum yield of PSII (Y II ) indicates the part of the energy absorbed by chlorophyll, which is associated with PSII and is used in the photochemical activity, evidencing the sum of transported electrons and, thus, becomes an indicator for photosynthesis (Lichtenthaler et al, 2005;Jiménez-Suancha et al, 2015). Overall, the Y II of the waterlogged lulo plants decreased with the increased stress, as Else et al (2009) observed in tomatoes.…”
Section: Chlorophyll Fluorescence Parametersmentioning
confidence: 96%
“…Photochemical quenching (qP) quantifies the photochemical capacity of PSII and refers to the proportion of excitation energy trapped by open PSII reaction centers (Lichtenthaler et al, 2005;Hanelt, 2018). While non-photochemical quenching (NPQ) indicates the activation of non-photochemical processes that lead to the dissipation of non-radiant energy, such as changes in the transthylacoidal pH gradient, photoinhibition, interruption of light collection complexes, and formation of zeaxanthin, among others (Jiménez-Suancha et al, 2015;Rohaček, 2002).…”
Section: Chlorophyll Fluorescence Parametersmentioning
confidence: 99%
“…This dissipation of excess radiant energy as heat in the complex PSII antenna is a photoprotection induced by light through the thermal dissipation of energy. This is carried out in the xanthophyll cycle (Jiménez-Suancha et al, 2015, Ping et al, 2015. Furthermore, the increases were 388.5% at 17 DD, 484.3% at 21 DD, and 398.0% at 38 DD.…”
Section: Chlorophyll Fluorescencementioning
confidence: 99%
“…Se observaron diferencias significativas en el factor Si y en la interacción Si × S, sobre la Fm en los horarios de 9:00 y 15:00 h (p˂ 0.05) (Cuadro 4). Adicionalmente la salinidad provocada por la adición de NaCl incrementó los valores de Fm reflejo en la reducción de 'cierre' de los centros de reacción del PSII (González et al, 2008), lo que a su vez implica una mayor activación de las reacciones fotoquímicas (Jiménez-Suancha et al, 2015). Lo anterior, refuerza la hipótesis de que el daño por salinidad presentado en los cultivos es resultado de la utilización del NaCl más que por una solución nutritiva balanceada (SNS).…”
Section: Fluorescencia Máxima (Fm)unclassified